2021
DOI: 10.31165/nk.2021.141.662
|View full text |Cite
|
Sign up to set email alerts
|

Deep Mediatization during COVID-19: An Interview with Professor Andreas Hepp, University of Bremen

Abstract: An Interview with Professor Andreas Hepp, University of Bremen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Mediatization entails the "transformation of many disparate social and cultural processes into forms or formats suitable for media representation" (Couldry, 2008, p. 50), a process which we also observed in this industry during the pandemic. Andreas Hepp (2013) points to the fact that the pandemic period was characterised by several processes of mediatization, including the repeat suggestions of "media-based 'solutions'" to (individual) problems (Kumar Putta & Anderson, 2021), which we observe also in the funeral industry, albeit more of necessity than inclination. In related areas, other research-Article: Covid-19 and the mediatization of the funeral industry in Australia and Denmark Stine Gotved, Hannah Gould & Lisbeth Klastrup ers have pointed to the acceleration of mediatization also in the religious sphere during the pandemic.…”
Section: Mediatization In the Funeral Industrysupporting
confidence: 54%
“…Mediatization entails the "transformation of many disparate social and cultural processes into forms or formats suitable for media representation" (Couldry, 2008, p. 50), a process which we also observed in this industry during the pandemic. Andreas Hepp (2013) points to the fact that the pandemic period was characterised by several processes of mediatization, including the repeat suggestions of "media-based 'solutions'" to (individual) problems (Kumar Putta & Anderson, 2021), which we observe also in the funeral industry, albeit more of necessity than inclination. In related areas, other research-Article: Covid-19 and the mediatization of the funeral industry in Australia and Denmark Stine Gotved, Hannah Gould & Lisbeth Klastrup ers have pointed to the acceleration of mediatization also in the religious sphere during the pandemic.…”
Section: Mediatization In the Funeral Industrysupporting
confidence: 54%
“…In crisis situations such as the pandemic the demand for information is very high and what we know today about the pandemic is communicated to us through media (Putta & Anderson, 2021). Yet, in the wake of the pandemic, identifying the source of information became more important again, due to the spreading of misleading information, conspiracy theories, and fake news, that were spread (among others) by alternative news media.…”
Section: Acquisition Of Cultural Capital: Accessing and Disseminating...mentioning
confidence: 99%
“…Hepp, Breiter and Hasebrink (2018b) claim that in the current wave we have now reached a stage of deep mediatization, which shows how deeply our everyday practices are interrelated with mediated practices. The effects of deep mediatization have been accelerated by the pandemic (Putta & Anderson, 2021). Due to the reduction of direct social contacts, we received most of our information via (digital) media and communication became further mediated in all fields of society where direct social contact was not relevant in order to keep the infrastructure critical for the sustainment of state and society going.…”
Section: Introductionmentioning
confidence: 99%
“…Most recent studies on the information crisis, or the 'post-truth' crisis, where people are more likely to accept an argument based on their emotions and beliefs rather than one based on facts (González-Méijome 2017), have dealt with analyzing the content and spread of fake news. According to Hepp (Hepp cited by Kumar Putta and Anderson 2021), what we know about the coronavirus is communicated to us through the media. Chavda et al (2022) revealed that during the COVID-19 crisis, people started to believe false news, took home remedies and believed fraudulent health claims on social media.…”
Section: Introductionmentioning
confidence: 99%